Superprotonic Conductivity in Flexible Porous Covalent Organic Framework Membranes. (19th July 2018) - Sasmal, Himadri Sekhar; Aiyappa, Harshitha Barike; Bhange, Siddheshwar N.; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar; Banerjee, Rahul
Abstract: Poor mechanical stability of the polymer electrolyte membranes remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p ‐toluene sulfonic acid loaded COF membranes (COFMs) show the highest proton conductivity (as high as 7.8×10 −2  S cm −1 ) amongst all crystalline porous organic polymeric materials reported to date, and were tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm −2 power density, which is the highest among COFs and MOFs, highlights the possibility of using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.